The application of quality requirements in the Ministry of Labour and Social Affairs using the international standard (ISO 9001: 2015) Korean case study of the Iraqi Center - حافظ, عبد الناصر علك; فرمان, قتيبة ناظم (Journal of Economics and Administrative Sciences, 2017)
This research aims to study the mechanism of application of international specification requirements (ISO 9001: 2015) at the Iraqi Center- Korean Vocational Training return to vocational training department at the Ministry of Labour and Social Affairs for the purpose of preparing and creating the center to get a certificate of conformity with the requirements of the standard (ISO 9001: 2015) that would elevate the level of performance and services provided in the respondent Center after it is identified and the study of the reality of the quality management system by identifying strengths and weaknesses in the system to diagnose the gap and find ways to address that gap, and adopted the researchers the case study method to conduct the search, and was the use of checklists (CHICK LIST) private international has been stated (IS0 9001: 2015) and through the field of cohabitation and conducting interviews and access to records and documents were necessary data collection as it has been to measure the application and documentation based on percentages, the arithmetic mean is likely, he found a number of results most notably the adoption of the senior leadership of the practices of quality and willingness to apply the international standard requirements, owning a place basic infrastructure to qualify from the application requirements of the standard, and the possession of employees at the center of expertise and skills that will qualify them to provide better services, but the failure of the center using a practical approach and thinking is based on the risks and opportunities as a context work practice in all actions within the center, particularly in the training process provided for the trainees that, there is a difference in perception employing the concepts of measures to meet labor market needs in terms of identifying needs and speed of response to changes in the external environment as well as an overlap in the planning process for the system of quality management center.